2009
DOI: 10.1111/j.1365-2591.2009.01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonic extracts from a bacterium related to periapical disease activate gelatinase A and inactivate tissue inhibitor of metalloproteinases TIMP‐1 and TIMP‐2

Abstract: These findings suggest that P. gingivalis SBE may cause connective tissue to be destroyed, contributing to the process of periapical disease, by activating pro-MMP-2 as well as by inactivating TIMP-1 and TIMP-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Plaque rupture, leading to leakage of the prothrombotic plaque core in the circulation and thrombus formation, can be due to the bacteria-dependent release of matrix metalloproteinases with concomitant suppression of the matrix metalloproteinase antagonist, tissue inhibitor of metalloproteinases [84,85]. …”
Section: Proatherogenic Sequelae Of Bacterial Presence In Vascular Cellsmentioning
confidence: 99%
“…Plaque rupture, leading to leakage of the prothrombotic plaque core in the circulation and thrombus formation, can be due to the bacteria-dependent release of matrix metalloproteinases with concomitant suppression of the matrix metalloproteinase antagonist, tissue inhibitor of metalloproteinases [84,85]. …”
Section: Proatherogenic Sequelae Of Bacterial Presence In Vascular Cellsmentioning
confidence: 99%
“…MMPs play an important role during periapical pathology development (1113), and it has been suggested that the modality of root canal treatment could interfere with MMPs expression (14). Moreover, elevated MMP levels have also been reported to correlate with non-healing (15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…Without prior demineralization, it is unlikely that bacterial enzymes can affect dentinal collagen protected by minerals: even in periodontal diseases, host‐derived MMPs instead of bacterial proteases are considered key players in the extracellular matrix degradation and bacterial proteases have been shown not to be directly involved in root dentin destruction. However, they might be able to activate host proteolytic enzymes , which in turn may under certain conditions degrade the organic matrix of dentin. In 2009, using a gelatin zymography assay, Itoh and co‐workers showed that whole‐cell extracts from Prevotella nigrescens , an anaerobe Gram‐negative species regularly found in the microflora of infected root canals , could noticeably activate pro‐MMP‐2 and pro‐MMP‐9, both gelatinases that are found in coronal and root dentin , and could play an important role in the degradation of dentin collagen fibrils .…”
Section: Dentin Management: Microbial and Biofilm Factors Altering Thmentioning
confidence: 99%